?EFFICACY OF IVERMECTIN AGAINST SARCOPTIC MANGE IN CAMEL - MAQBOOL, A.; . ATHAR, M; SHAKOOR, A. (Biological Sciences - PJSIR, 1996)
Iverraectin at the dose rate of 0.2 mg/kg body weight and 0.4 mg/kg body weight as subcutaneous injection repeated 3 times at 15 days interval proved to be 100% effective against light, medium and heavy infestation of sarcoptic mange in camels. No side effects were observed with this drug. The untreated control animals remained positive for mange throughout the course of treatment.